Neoliberalism and their effects on public health services: The case of health workers facing the covid-19 pandemic - Juárez, Nayeli Pérez; Negreros Amaya, Gonzalo Esteban; Jiménez, Carlos Alberto (Revista Internacional de Salarios Dignos, 2022)
Neoliberalism weakened the public health system, and the pandemic reflected the contradictions of its neglect. The objective of the work is to analyze the relationship between the structural conditions that neoliberalism has generated in public health services and its impact on the working conditions of health personnel who treated patients infected with covid-19. The methodology used is descriptive statistics with information from primary sources through a questionnaire of 23 items for convenience and secondary sources from INEGI, WHO, OECD and ECLAC. The questionnaire was applied from December 2020 to January 2021, given the sanitary conditions, it was applied electronically, taking care of the confidentiality of the worker. The main results are: the increase in the working day from 8 to 12 hours a day, regular salary perception, which implied that employees must have a second job in 36%, the risk of work increased, 100% of the sample had an infected colleague and 83% a colleague who died, in terms of health protection, 40% considered it insufficient, 98.4% of the sample has high stress, which deteriorates the worker’s living conditions. The implications are serious for the country and for workers who work in adverse conditions, the needs of the sector must be met immediately, increasing the budget for infrastructure and promoting the specialization of workers.